ANALISA VARIABEL KEGAGALAN DALAM PROSES PENGADAAN PEMILIHAN PENYEDIA JASA PELAKSANA KONSTRUKSI SECARA ELEKTRONIK ( E- PROCUREMENT ) DI KOTA PEKANBARU - Djuniati, Sri; Komara, Rian Tri; WahyuDyah, Ni (Proceedings ACES (Annual Civil Engineering Seminar), 2015)
E-procurement is a process of procuring goods and services which is done electronically(internet/web based). One of the steps worth noted in construction project is the process ofcontractor appointment. Usually, such process is conducted through the auction of services andgoods procurement. The auction is currently regulated in Presidential Regulation of 2012Number 70 about the second amandement of Presidential Regulation of 2010 Number 54about Procurement of Government Services and Goods. In accordance to the regulation, thisresearch aims to identify failure variables that can affect the process of evaluation forconstruction services auction in government owned project especially in Pekanbaru, Riau. Datain this research is obtained from interview with the Head of ULP and LPSE of Riau Provinceand also secondary data obtained from LPSE of Riau Province’s website that comprise ofdocuments regarding the implementation of the auction especially in road and pavementconstruction service on 2011, 2012 and 2013. The method used to process the data is manualprocess using software aid of Microsoft Excel, pie chart and bar chart.According to the resultof the analysis conducted on auction for road and pavement construction service between 2011until 2013, it can be obtained that the biggest percentage of 44% during 2011 is foradministration phase,the dominant factor of contractorfailurebecause they were not uploadeddocument of demand.In 2012, the biggest percentage of 48% of the contractor failure causedby technical problems in construction method and where in 2013 with the same the dominantfactor of contractor failure increased to 51%.Kata kunci: auction, E-procurement, failure factor, services and goods procurement system.